2016
DOI: 10.1007/s00412-016-0605-6
|View full text |Cite
|
Sign up to set email alerts
|

Transvection in Drosophila: trans-interaction between yellow enhancers and promoter is strongly suppressed by a cis-promoter only in certain genomic regions

Abstract: Transvection is a phenomenon of interallelic communication whereby enhancers of one allele can activate a promoter located on the homologous chromosome. It has been shown for many independent genes that enhancers preferentially act on the cis-linked promoter, but deletion of this promoter allows the enhancers to act in trans. Here, we tested whether this cis-preference in the enhancer-promoter interaction could be reconstituted outside of the natural position of a gene. The yellow gene was chosen as a model sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
2
1
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 57 publications
1
5
0
Order By: Relevance
“…(4b) The presence of a promoter in cis to the enhancer reduces its effectiveness in transvection. This cis-preference phenomenon, which has been described before (Geyer et al 1990;Martínez-Laborda et al 1992;Hendrickson and Sakonju 1995;Casares et al 1997;Sipos et al 1998;Morris et al 1999aMorris et al ,b, 2004Bateman et al 2012a;Kravchuk et al 2017), depends on the activity of the cis-linked promoter: we have shown that the TATA element seems to play a more important role than the DPE in inhibiting a cis-linked enhancer from acting in trans. (4c) The GI is highly asymmetric with 12 Su(Hw) binding sites all in the same orientation: the GI orientation with respect to the enhancer-promoter interacting pair is important, although not crucial for the transvection outcome.…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…(4b) The presence of a promoter in cis to the enhancer reduces its effectiveness in transvection. This cis-preference phenomenon, which has been described before (Geyer et al 1990;Martínez-Laborda et al 1992;Hendrickson and Sakonju 1995;Casares et al 1997;Sipos et al 1998;Morris et al 1999aMorris et al ,b, 2004Bateman et al 2012a;Kravchuk et al 2017), depends on the activity of the cis-linked promoter: we have shown that the TATA element seems to play a more important role than the DPE in inhibiting a cis-linked enhancer from acting in trans. (4c) The GI is highly asymmetric with 12 Su(Hw) binding sites all in the same orientation: the GI orientation with respect to the enhancer-promoter interacting pair is important, although not crucial for the transvection outcome.…”
Section: Discussionsupporting
confidence: 64%
“…B1 and B2 for e8, and B3 and B4 with B5 for e7). This came as no surprise, since numerous earlier studies on transvection have indicated that an enhancer's action in trans is suppressed by the presence of a promoter in cis (Geyer et al 1990;Martínez-Laborda et al 1992;Hendrickson and Sakonju 1995;Casares et al 1997;Sipos et al 1998;Morris et al 1999aMorris et al ,b, 2004Bateman et al 2012a;Kravchuk et al 2017). Different promoters of varying core element composition have been reported to display cispreference (i.e., to attenuate transvection).…”
Section: Transvection Is Weaker Than Cis Enhancer-promoter Activity and Is Suppressed By Promoter Cis-preferencementioning
confidence: 95%
“…Transgenic systems have thus far been used to demonstrate that the Drosophila genome is generally permissive to transvection ( Chen et al . 2002 ; Kravchuk et al . 2016 ; King et al .…”
Section: Introductionmentioning
confidence: 99%
“…(4b) The presence of a promoter in cis to the enhancer reduces its effectiveness in transvection. This cispreference phenomenon, which has been described before (Geyer et al 1990;Martínez-Laborda et al 1992;Hendrickson and Sakonju 1995;Casares et al 1997;Sipos et al 1998;Morris et al 1999a;b, 2004;Bateman et al 2012a;Kravchuk et al 2016), depends on the activity of the cis-linked promoter: I have shown that the TATA element seems to play a more important role than the DPE in inhibiting a cis-linked enhancer from acting in trans. (4c) The GI is highly asymmetric with 12 Su(Hw) binding sites all in the same orientation: the GI orientation with respect to the enhancer-promoter interacting pair is important, although not crucial for the transvection outcome.…”
Section: Discussionmentioning
confidence: 83%
“…In the above experiments I noticed that confronting an enhancerless reporter in trans to a solitary enhancer gave more robust expression compared to all my previous experiments, where the transvecting enhancer was linked in cis to a promoter (Figure 37, compare B1 to B2 for e8, and, B3 and B4 to B5 for e7). This came as no surprise, since numerous earlier studies on transvection have indicated that an enhancer's action in trans is suppressed by the presence of a promoter in cis (Geyer et al 1990;Martínez-Laborda et al 1992;Hendrickson and Sakonju 1995;Casares et al 1997;Sipos et al 1998;Morris et al 1999a;b, 2004;Bateman et al 2012a;Kravchuk et al 2016). Different promoters of varying core element composition have been reported to display cis-preference (i.e.…”
Section: Transvection Is Weaker Than Cis Enhancer-promoter Activity and Is Suppressed By Promoter Cis-preferencementioning
confidence: 96%